Analisis Rantai Pasok dan Nilai Tambah Agroindustri Kopi Lasi Selaras Alam di Kabupaten AgamProvinsi Sumatera Barat - Rizki Ananda; Farida Hanum Hamzah; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This research was aimed to analyze the flow of supply chain, value-added, and determined the strategy for improvement of supply chain performance in Lasi Coffee Selaras Alam. This research was conducted in Agam District, West Sumatera. A purposive method was used to decide the location of this research. This research used a questionnaire that was distributed to 20 respondents consisting of 15 coffee farmers, 2 merchant collectors, and 3 stakeholders of the Selaras Alam Cooperative. The method used for this research was descriptive, namely Hayami value-added analysis and SWOT and AHP analysis. The result of this research showed that the involved parties in the agroindustry of lasi coffee supply chain were farmers, collectors, and consumers. Value-added obtained by farmers from the processing of one kilogram of coffee fruit into coffee beans were 3,560 IDR (41.59%) and value-added obtained by merchant collectors from sorting one kilogram of coffee beans were 20,600 IDR (19.51%). The strategy to improve the supply chain performance of Lasi Coffee Agroindustry was to improve the quality and the production and maintainedthe consistency of the brand (0.302).Keywords: lasi coffee, supply chain, value added, SWOT, AHP